The Metanarrative of Postmodernism? The Apories of Emancipated Thought - Szkaradnik, Katarzyna (Hybris, 2012)
Because the assumptions of postmodernism are something obvious, the authoress decided to look at this obviousness in order to examine its second bottom, like deconstructionism does. Postmodernism speaks out against fundamentalism, universal truths as well as metaphysical notions. According to Lyotard, these notions were related with each other in totalizing metanarratives, that is tales including liberating teleology focused on the Freedom and the Truth. The end of these optimistic ideas was a result of the experience of Auschwitz and totalitarianism. Today, although postmodernism shows itself as an anti-dogmatic orientation, it became a predominant theory. So as “speculative metanarrative” it legalizes knowledge, imported to its own discourse. It propagates – as universal and irrefutable – the truth about relativism and the mediatization of reality, but on the other hand, in the face of the melting of “I” in fiction by the economy, it turns out that postmodernists long for “mythical” times of plenitude. The eschatological dimension seems to be the most important component of metanarratives and in postmodernism it manifests in the apotheosis of Different and the responsibility, liberating impetuses and the deepening of the spirituality. Such “independence metanarrative” does not concern the “nation” any more, but every of us, equally deserving worry and compassion. Postmodernism wants to become a leading thought of our times, which require of us, as Bauman writes, to alter our casualness in destination. It turns out, that the hidden background of postmodernism is the pursuit of wholeness, but not annihilating totality. The cracks and margins have to be a shield against the fate and make up the foundation of the eschatological hope of postmodernism.